2016
DOI: 10.4137/grsb.s39076
|View full text |Cite
|
Sign up to set email alerts
|

Community-Reviewed Biological Network Models for Toxicology and Drug Discovery Applications

Abstract: Biological network models offer a framework for understanding disease by describing the relationships between the mechanisms involved in the regulation of biological processes. Crowdsourcing can efficiently gather feedback from a wide audience with varying expertise. In the Network Verification Challenge, scientists verified and enhanced a set of 46 biological networks relevant to lung and chronic obstructive pulmonary disease. The networks were built using Biological Expression Language and contain detailed i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In this context, with the help of powerful bioinformatic tools, several studies have tried to predict different molecular pathways that are directly related lncRNAs, miRNAs, and genes, which have increased the knowledge about interactions between that kind of molecules [ 33 , 34 ]. It is worth mentioning that several databases have been created to systematize and visualize causal relationships between asthma and lung disease [ 35 , 36 ]. Although mathematics and computer science have helped generate much new knowledge in biological sciences, there is still a long way to go, and indeed in the future, much more powerful software and algorithms will be created to help advance disease research.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, with the help of powerful bioinformatic tools, several studies have tried to predict different molecular pathways that are directly related lncRNAs, miRNAs, and genes, which have increased the knowledge about interactions between that kind of molecules [ 33 , 34 ]. It is worth mentioning that several databases have been created to systematize and visualize causal relationships between asthma and lung disease [ 35 , 36 ]. Although mathematics and computer science have helped generate much new knowledge in biological sciences, there is still a long way to go, and indeed in the future, much more powerful software and algorithms will be created to help advance disease research.…”
Section: Discussionmentioning
confidence: 99%
“…A wide spectrum of antimicrobial activities of AMPs inspires researchers to search for new active peptides in biological material [ 252 , 253 ], and also serves as the basis for the design of new synthetic compounds [ 254 , 255 ]. To date, information about AMPs is presented in numerous databases describing the structural, functional, allergenic and toxicological properties of these peptide factors of innate immunity [ 256 , 257 , 258 , 259 , 260 ]. The tools of modern bioinformatic approaches allow one to perform an in-depth analysis of structural homology in order to search for new, not yet discovered AMPs, and also offer additional methods for predicting a putative biological activity in silico [ 261 , 262 , 263 , 264 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been confirmed that IARR-Anal10 suppressed the virulence of K. pneumoniae to a degree similar to tigecycline, used to treat carbapenemresistant Enterobacteriaceae infections, and did not induce the development of resistance by K. pneumoniae [160]. Notably, AMPs from amphioxus were discovered using bioinformatics and systems biology, which integrate research data and serve as a basis for drug design and novel AMPs [161,162]. It was found that the amphioxus ribosomal polypeptide RPS23, designated as BjRPS23, acted not only as a pattern recognition receptor (PRR) capable of identifying LPS, LTAs, and PGN, but also as an effector killing Gram-negative and Grampositive bacteria.…”
Section: Cephalochordatamentioning
confidence: 93%